“Let’s Benkyou”: Japanese Language Learning App - Chan, Zhi Ren; Hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2024)
As Japanese influence grows in Malaysia, whether culturally, educationally, or commercially, more people wish to learn the Japanese language. As a result, the "Let's Benkyou"Japanese language mobile learning app was created to assist such persons in beginning their learning journey. To develop this application, the Prototype Model is used as the project methodology. Before developing the application, the problem statements, the objectives and all the application requirements were identified. The Dart programming language and the Flutter framework were used to develop this application. The database is built using the Firebase platform. The application is hoped to help people to study Japanese in an effective way.